2025年2月4日 星期二

多項式,替換新變數

 GPT Icon

We are given the equation:

(x23x)214(x23x)+40=0(x^2 - 3x)^2 - 14(x^2 - 3x) + 40 = 0

Step 1: Substituting a New Variable

Let:

y=x23xy = x^2 - 3x

Then, our equation transforms into:

y214y+40=0y^2 - 14y + 40 = 0

Step 2: Solve the Quadratic Equation

The quadratic equation:

y214y+40=0y^2 - 14y + 40 = 0

can be solved using the quadratic formula:

y=(14)±(14)24(1)(40)2(1)y = \frac{-(-14) \pm \sqrt{(-14)^2 - 4(1)(40)}}{2(1)} y=14±1961602y = \frac{14 \pm \sqrt{196 - 160}}{2} y=14±362y = \frac{14 \pm \sqrt{36}}{2} y=14±62y = \frac{14 \pm 6}{2}

Step 3: Find Values of yy

y=14+62=202=10y = \frac{14 + 6}{2} = \frac{20}{2} = 10
y=1462=82=4y = \frac{14 - 6}{2} = \frac{8}{2} = 4

Thus, we have two equations to solve:

x23x=10x^2 - 3x = 10
x23x=4x^2 - 3x = 4

Step 4: Solve for xx

Equation 1: x23x10=0

Factorizing:

(x5)(x+2)=0(x - 5)(x + 2) = 0
x5=0orx+2=0x - 5 = 0 \quad \text{or} \quad x + 2 = 0
x=5orx=2x = 5 \quad \text{or} \quad x = -2

Equation 2: x23x4=0

Factorizing:

(x4)(x+1)=0(x - 4)(x + 1) = 0
x4=0orx+1=0x - 4 = 0 \quad \text{or} \quad x + 1 = 0
x=4orx=1x = 4 \quad \text{or} \quad x = -1

Final Answer

x=5,2,4,1

沒有留言:

張貼留言